A Report on Safe Use of the Internet: Some of the Most Common Risks. - Hughes, Todd F. (Hispania, 2008)
The Internet serves as the principal source for authentic materials for use in teaching. In addition to serving as an infinite realia bank for instructors, it also serves as a communication tool that has diminished the distances between classrooms and the target culture. Unfortunately, use of this medium is not fail safe. In terms of your computer's health, Cyberspace can be a dangerous realm.